Analisis Perilaku Seksual pada Anak dalam Pandangan Pendidikan Islam di Kota Bengkulu:Persfektif Pelaku, Korban dan Lokasi Kejadian - Asniti Karni; Hermi Pasmawati; Dilla Astarini (UIN Fatmawati Sukarno Bengkulu, 2023)
The findings of the study show that sexual behavior in children, judging from the characteristics of perpetrators and victims, tends to be carried out by perpetrators or vulnerable victims for all ages, education has a tendency to have the potential for all starting from kindergarten-university, economic conditions of both perpetrators and victims, trends in the conditions of the lower middle economic class, working conditions of parents, traders, laborers, self-employed and gardeners, Triggering factors of the perpetrator, exposure to pornography since elementary school, the influence of friends, and relationships that are not harmonious with partners. Meanwhile, the victim tends to be persuaded by people who have emotional closeness, the persuasion of a boyfriend, and the existence of a power relationship. Meanwhile, the location of the incident, everything has the potential to happen. Still, the tendency of the location that has become prevalent is, places far from supervision, quiet, in playgrounds, in the homes of victims or perpetrators, public spaces, and there are even some cases in quiet places of worship. Based on the results of these findings, it is recommended to protect children from sexual violence, the collaboration of all parties is needed. Governments, educational institutions, and communities must increase surveillance, provide child-friendly facilities, and provide education about self-protection. Parents, religious institutions, and law enforcement are expected to strengthen supervision, emotional relationships, and law enforcement to create a safe environment for children.